Learning English for specific purposes (ESPs) through social media platforms (SMPs): a systematic review - Rasha Abdullah Alshaye; Amr Selim Wannas; Mohamed Saeed Bakr (Journal of Innovative Digital Transformation)
Purpose – The search for new techniques to teach English nowadays has been more than ever. These techniques have to be interesting and enjoyable in order to lower the anxiety levels of students when learning English (Bakhsh, 2016). That is why many scholars and teachers look forward to integrating technology into language teaching. Social media platforms (SMPs) are among these techniques since millions of people around the world utilize them for daily interaction. Yet, teaching English for specific purposes (ESPs) relies on learners’ needs and employs an eclectic approach in delivering its course content. For this reason, the current study reviewed articles that tackled the topic of teaching or learning ESP from SMPs so as to uncover their effect and the attitude or motivation of learners. Design/methodology/approach – The researchers used the PRISMA flowchart model in order to identify, screen and include articles in the study. Findings – The results revealed that SMPs are effective in teaching and learning ESP writing, speaking and vocabulary. Yet, the included studies showed that learners’ attitude toward SMPs is positive as they believe that they are motivating and interesting. Research limitations/implications – Some aspects of social media have turned out to be beneficial in the learning process and they need further investigation from ESP practitioners and scholars. Originality/value – According to the study, it is crystal clear that the various social networks and platforms are beneficial and helpful for improving ESP productive skills.